The causality between intestinal flora and allergic diseases: Insights from a bi-directional two-sample Mendelian randomization analysis - Jin, Qiubai; Ren, Feihong; Dai, Dan; Sun, Nan; Qian, Yiyun; Song, Ping (Frontiers in Immunology, 2023)
Background Growing evidence shows a significant association between intestinal flora and allergic diseases, specifically atopic dermatitis (AD), allergic rhinitis (AR), and allergic asthma (AA). However, the causality has not yet been clarified. Objective We conducted a bidirectional two-sample Mendelian randomization (TSMR) analysis to study the causal relationships between intestinal flora classification and AD, AR, or AA. Materials and methods We obtained summary data of intestinal flora, AD, AR, and AA from a genome-wide association research. The inverse-variance weighted method is the primary method for analyzing causality in the TSMR analysis. Several sensitivity analyses were conducted to examine the stability of TSMR results. Reverse TSMR analysis was also performed to assess whether there was a reverse causality. Results A total of 7 bacterial taxa associated with AD, AR, and AA were identified by the current TSMR analysis. Specifically, the genus Dialister(P=0.034)and genus Prevotella(P=0.047)were associated with a higher risk of AD, whereas class Coriobacteriia (P=0.034) and its child taxon, order Coriobacteriales (P=0.034) and family Coriobacteriaceae (P=0.034), all had a protective effect on AR. In addition, the family Victivallaceae (P=0.019) was identified as a risk factor for AR. We also noticed a positive association between the genus Holdemanella (P=0.046) and AA. The reverse TSMR analysis didn’t suggest any evidence of reverse causality from allergic diseases to the intestinal flora. Conclusion We confirmed the causal relationship between intestinal flora and allergic diseases and provided an innovative perspective for research on allergic diseases: targeted regulation of dysregulation of specific bacterial taxa to prevent and treat AD, AR, and AA.